Improve Teacher Performance Development In Developing The Lesson Plans To Get The Quality Of Effective Education And Efficient In Smpn 04 Koto Xi Tarusan - Jafrizal Jafrizal (Fakultas Sastra Universitas Ekasakti, 2018)
Basically the task of teachers to educate, teach, train and evaluate students, so that learners can become human beings who can carry out life in harmony with his nature as a human being. related to the task of teachers in evaluating the students then the teacher should have the teaching skills. It is therefore necessary for the principal's role to motivate teachers to improve their performance and objectives to help teachers clearly see the purpose of education and to achieve the educational goals by fostering and developing better teaching methods and procedures. The purpose of this study is to increase the competence of teachers in order to devote time and energy to streamline learning. Improving ability in solving problems in teaching and learning in preparing RPP at SMP Negeri 04 Koto XI Tarusan January 2017.